Testing new accessions of guinea grass (Panicum maximum) for acid soils and resistance to spittlebug (Aeneolamia reducta) - Thomas, D.; Lapointe, Stephen L. (1989)
Adaptation of new accessions of Panicum maximum to an acid Oxisol (pH 4.8, 90% AI saturation) was assessed over 3 years on 2 sites of contrasting soil texture at the Carimagua Research Station, in the Eastern Plains of Colombia. Twenty-seven lines, selected originally from a collection of 436 accessions, were evaluated along with 2 commercial cultivars as controls. Concurrently, a pot trial was established in the glasshouse at CIAT, Palmira Colombia to test the accessions for resistance to spittlebug (Aeneolamia reducta). At the 2 sites, 6 accessions produced significantly more green leaf dry matter than the controls. Accessions CIAT 6799, 6944, 16019 and 16042 were amongst the highest yielding lines at both sites, despite wide variation in soil texture. In vitro digestibility values did not vary significantly from those of the controls. The incidence of plant diseases and spittlebug in the field trial was low. In the glasshouse, emergence of spittlebug adults (a measure of antibiosis) reared on 10 of the accessions (including CIAT 6799 and 16042) was less than that of spittlebugs reared on a resistant control. Foliar damage was correlated significantly with adult emergence. Practical implications of the results are discussed.